A computed tomography–based morphometric analysis of thoracic pedicles in a European population - Alberto Alfieri Zellner; Christian Prangenberg; Jonas Roos; Soufian Ben Amar; Tamara Babasiz; Christopher Wahlers; Peer Eysel; Johannes Oppermann (Journal of Orthopaedic Surgery and Research)
Abstract Purpose The goal of this retrospective study was to perform a CT imaging assessment of thoracic pedicles to provide a representative understanding of pedicle morphology for pedicle-based fixation systems commonly used in orthopedics, trauma and neurosurgery. This study aimed to better understand the morphology of the spine and give spine surgeons a better understanding of thoracic spine anatomy. Methods In this study, we retrospectively measured the thoracic spine pedicles of a total of 16 males and 16 females, totaling in 768 individual pedicles. For the measurements, we used standardized planes in computed tomography imaging with a maximum slice thickness of 1 mm. Results In brief, we identified significant differences in various measurements of male and female pedicle morphology. The medial cortical wall of the pedicles was significantly thicker than the lateral wall, and, in both sexes, the thoracic vertebral body number four was the vertebra with the least amount of cortical bone in the pedicle. Conclusions Surgeons performing operations involving pedicle screw placement should be aware of the sex-specific differences in thoracic spine pedicle morphology noted in this research.